Optimalisasi Database 3.0 untuk Verifikasi Data Pelatihan Pelaut - Nugraha, Rizal Fitrah; Henderi, Henderi; Sudaryono, Sudaryono (JTERA (Jurnal Teknologi Rekayasa), 2024)
This study explores the optimization of Database 3.0 to enhance the registration of training participants and data verification in seafarer training programs. The increasing complexity of managing and verifying vast training data demands advanced database technologies. Database 3.0, with its capabilities for real-time updates, automated data entry, and system integration, presents a solution to these challenges. The research employs SmartPLS to model the relationships between Database Optimization, Data Accuracy, Verification Efficiency, and User Satisfaction, aiming to assess how optimization impacts the overall effectiveness of training data management. The study fills a gap in the literature by focusing on Database 3.0 optimization within the maritime training context, an underexplored area. The results indicate that optimized databases significantly improve data accuracy and verification efficiency, leading to higher user satisfaction among administrators and trainers. The findings suggest that integrating Database 3.0 into seafarer training programs can streamline data verification processes, ultimately enhancing certification reliability and operational efficiency in maritime education. These insights offer a novel perspective on utilizing advanced database technologies in specialized sectors like maritime training.